The correlation between knowledge, family income and peer support with anaemia prevention behaviour among adolescent girls - Triharini, Mira; Tanfidiah, Enis; Wahyuni, Erna Dwi; Dewi, Yulis Setiya; Gouda, Amel Dawod Kamel (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the correlation of knowledge, family income and peer support with anaemia preventive behaviour among adolescent girls. Method: The correlational, cross-sectional study was conducted at the Junior High School 3, Sampang, Indonesia, from April to June 2021, and comprised adolescent girls who had gone through menarche and were living with their families. Data was collected using knowledge, peer support and anaemia preventive behaviour questionnaires that were designed based on literature. Data was analysed using Spearman’s Rho test. Results: Of the 156 subjects with mean age 14.0±0.98 years, 60(38.5%) were studying in the 8th grade. The mean age of menarche was 11.91±1.03 years. Anaemia preventive behaviour was significantly associated with knowledge (p=0.000, r=0.277) and peer support (p=0.000, r=0.403), but not with family income (p=0.166, r=0.111). Conclusion: knowledge level and better peer support were found to improve anaemia preventive behaviour among adolescent girls. Keywords: Anaemia, Iron, Adolescent, Incidence.